2015
DOI: 10.1038/ki.2014.394
|View full text |Cite
|
Sign up to set email alerts
|

Renal developmental defects resulting from in utero hypoxia are associated with suppression of ureteric β-catenin signaling

Abstract: Gestational stressors, including glucocorticoids and protein restriction, can affect kidney development and hence final nephron number. Since hypoxia is a common insult during pregnancy, we studied the influence of oxygen tension on kidney development in models designed to represent a pathological hypoxic insult. In vivo mouse models of moderate, transient, midgestational (12% O₂, 48 h, 12.5 dpc) or severe, acute, early-gestational (5.5-7.5% O₂, 8 h, 9.5-10.5 dpc) hypoxia were developed. The embryo itself is k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 57 publications
0
49
0
1
Order By: Relevance
“…However, the acid maceration technique was used to quantity nephron number, which is not as reliable as the physical-disector fractionator method, the current gold standard of glomerular number estimation . In a recent study, midgestation, moderate hypoxia (E12.5, 12% maternal O 2 ) for 48 hours in the mouse caused fetal growth restriction, suppression of branching morphogenesis in the kidney and reduced nephron number (Wilkinson et al, 2015). The same study also demonstrated that severe, short-term hypoxia (5.5-7.5% maternal O 2 for 10 h from E9.5-10.5) resulted in congenital abnormalities of the kidney and urinary tract.…”
Section: Effects Of Prenatal Hypoxia On the Kidneymentioning
confidence: 56%
See 4 more Smart Citations
“…However, the acid maceration technique was used to quantity nephron number, which is not as reliable as the physical-disector fractionator method, the current gold standard of glomerular number estimation . In a recent study, midgestation, moderate hypoxia (E12.5, 12% maternal O 2 ) for 48 hours in the mouse caused fetal growth restriction, suppression of branching morphogenesis in the kidney and reduced nephron number (Wilkinson et al, 2015). The same study also demonstrated that severe, short-term hypoxia (5.5-7.5% maternal O 2 for 10 h from E9.5-10.5) resulted in congenital abnormalities of the kidney and urinary tract.…”
Section: Effects Of Prenatal Hypoxia On the Kidneymentioning
confidence: 56%
“…We confirmed, using unbiased stereology, that the number of glomeruli per kidney in the male hypoxia-exposed mice was reduced by ~25%. This is an equivalent reduction in glomerular number to that seen in mice exposed to transient mid-gestational hypoxia (males and females combined) (Wilkinson et al, 2015), and in males offspring following uteroplacental insufficiency in the rat (Wlodek et al, 2007). However, female hypoxia-exposed offspring presented with number of glomeruli per kidney similar to that of the control offspring suggesting that gender is somewhat protective against the hypoxic insult induced throughout late gestation.…”
Section: Sex Specific Reductions In Nephron Number Following Prenatalmentioning
confidence: 74%
See 3 more Smart Citations